Effect of Fasting on Rumen Ecology in Feed Restricted Male Nubian Goat Kids (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to investigate the effect of fasting for 4 days on rumen ecology of Nubian goats after two levels of feed restriction (30% and 60% of ad libitum) for 6 weeks. Twelve male Nubian goat kids were divided into three groups according to the level of feed restriction; A (control; ad libitum feed consumption), B (30% feed restriction of ad libitum) and C (60% feed restriction of ad libitum) for 6 weeks. Thereafter, they were exposed to fasting (100% feed restriction) for 4 days. During fasting phase, the three groups showed a significant (p
Keywords: Goat; Feed restriction; Fasting; Rumen environment